Relationship between Intrinsic-Extrinsic Motivation, Transformational Leadership on Job Performance Through Employee Creativity: A Systematic Literature Review - Agus Dharmanto; Zahara Tussoleha Rony (Journal of Economics, Management, Entrepreneurship, and Business (JEMEB), 2023)
Intrinsic motivation is the motives that become active or function so that there is no need for external stimulation, because from within the individual there is an urge to do something. Meanwhile, extrinsic motivation is motives that are active and function due to external stimuli. Transformational leadership reflects the attitude of a participatory leadership that is not only able to motivate and move the organization vertically and horizontally, but also to create an organizational capacity that is always agile in every situation. While job performance is the result of work related to organizational goals, efficiency and other performance effectiveness performance. To see the results of the work, of course there are aspects that can be measured in it and Employee Creativity refers to the emergence of new and useful ideas for employees. Employees as members of the organization who are experienced in human resource practices, therefore the attitudes and behavior of employees depend on the management system implemented. This study aims to determine the influence of Intrinsic-Extrinsic Motivation and Transformational Leadership Relationships on Job Performance through Employee Creativity moderated by spiritual incentive. The type of research used is Systematic Literature Review research.